ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK DALAM MENYELESAIKAN SOAL MATERI MATRIKS BERDASARKAN TEORI WANKAT DAN OREOVOCZ - Ana Rajiyatul Muna; Sugiyanti; Nurina Happy; Fairuz Amin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this study is to analyze the mathematical problem-solving abilities of students in working on matrix material problems based on the theory of Wankat and Oreovocz with 7 stages of problem-solving strategies. The seven problem- solving stages are: the "I can" stage, the defining stage, the exploration stage, the planning stage, the doing stage, the checking stage, and the generalizing stage. This type of research is descriptive qualitative. The subjects of the research were 36 students from class XI-11 of SMA Negeri 9 Semarang. Data collection was conducted through tests and interviews. The students of class XI-11 were identified based on the results of their mathematical problem-solving abilities according to Wankat and Oreovocz's theory, and then 5 subjects were selected to represent each category. The results showed that students' problem-solving abilities can be divided into several categories: (1) students with very good problem-solving abilities can solve problems, define, explore, plan, do, check, and generalize; (2) students with good problem-solving abilities can solve problems, define, explore, plan, do, but the answers are still less accurate; (3) students with sufficient problem-solving abilities can solve problems, define, explore, plan, but there are still errors; (4) students with poor problem-solving abilities can solve problems, define, explore, and plan but are still less accurate; (5) students with very poor problem-solving abilities can only solve problems, explore, and define.